Implementasi Standar Pengelolaan Pendidikan Dalam Mencapai Tujuan Pendidikan Islam - Palahudin, Palahudin; Hadiana, Muhammad Eri; Basri, Hasan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Abstract. Islamic education is tasked with guiding and directing the development of students from one stage to another until it reaches optimal levels. Islamic education aims to create a perfect human (al-insanul kamil) and a good human being (al-insan al-shalih). Other tasks are in accordance with the vision and mission of the Prophet, namely perfecting human morals. A good education is certainly well managed. Therefore it is necessary to manage according to Islamic teachings. By using a qualitative descriptive research method, this study will try to dig deeper into the extent to which the achievement of education management standards in accordance with Islamic teachings and solutions to solve problems faced. The management of education in achieving the goals of Islamic education is education that is capable of making people who are faithful and devout, educating pious individuals by paying attention to spiritual, emotional, social, intellectual, physical development, educating members of pious social groups, both in the Muslim family and community.